Airway surface liquid acidification initiates host defense abnormalities in Cystic Fibrosis - Simonin, Juliette; Bille, Emmanuelle; Crambert, Gilles; Noel, Sabrina; Dreano, Elise; Edwards, Aurélie; Hatton, Aurélie; Pranke, Iwona; Villeret, Bérengère; Cottart, Charles-Henry; Vrel, Jean-Patrick; Urbach, Valérie; et al. (Scientific reports, 2019)
Cystic fibrosis (CF) is caused by defective Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) protein. Morbidity is mainly due to early airway infection. We hypothesized that S. aureus clearance during the first hours of infection was impaired in CF human Airway Surface Liquid (ASL) because of a lowered pH. The ASL pH of human bronchial epithelial cell lines and primary respiratory cells from healthy controls (WT) and patients with CF was measured with a pH microelectrode. The antimicrobial capacity of airway cells was studied after S. aureus apical infection by counting surviving bacteria. ASL was significantly more acidic in CF than in WT respiratory cells. This was consistent with a defect in bicarbonate secretion involving CFTR and SLC26A4 (pendrin) and a persistent proton secretion by ATP12A. ASL demonstrated a defect in S. aureus clearance which was improved by pH normalization. Pendrin inhibition in WT airways recapitulated the CF airway defect and increased S. aureus proliferation. ATP12A inhibition by ouabain decreased bacterial proliferation. Antimicrobial peptides LL-37 and hBD1 demonstrated a pH-dependent activity. Normalizing ASL pH might improve innate airway defense in newborns with CF during onset of S. aureus infection. Pendrin activation and ATP12A inhibition could represent novel therapeutic strategies to normalize pH in CF airways.